Arkivets demokratiska roll och New Public Management - Sjögren,Robert (2018)
This Master’s thesis explain the effects of New Public Management on the democratic role of the archives, and investigates how this is evident in the archive's governing and policy documents. It mainly uses renamed versions of Christopher Hood's (1991) seven doctrines of New Public Management to present New Public Management, as well as where they may be in conflict with Terry Eastwood's (2002) democratic ideals and practices, and laws for archival activities in Sweden. In the content analysis, the thesis look at swedish public archive's governing and policy documents and investigate how many of the seven doctrines are present. It then looks at the differences from documents from the 1970s to the documents that apply today. The older documents show, in all cases, fewer expressions for New Public Management.
Keywords: ALM; archival science; critical theory; democracy; new public management; public archives; content analysis; regulatory documents; policy documents; governing documents; ABM; arkivvetenskap; kritisk teori; demokrati; innehållsanalys; offentliga arkiv